2023
DOI: 10.3390/e25050765
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Basketball Game Outcome Prediction through Fused Graph Convolutional Networks and Random Forest Algorithm

Abstract: Basketball is a popular sport worldwide, and many researchers have utilized various machine learning models to predict the outcome of basketball games. However, prior research has primarily focused on traditional machine learning models. Furthermore, models that rely on vector inputs tend to ignore the intricate interactions between teams and the spatial structure of the league. Therefore, this study aimed to apply graph neural networks to basketball game outcome prediction, by transforming structured data int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Zhao et al [ 26 ] (2023) applied Graph Neural Networks (GNN) to predict basketball game outcomes by transforming structured data into unstructured graphs to reveal the complex passing interactions among players. By integrating machine learning algorithms with Graph Convolutional Network (GCN) models, they achieved a prediction accuracy rate of 71.54%, offering a novel perspective on team interactions.…”
Section: Related Studiesmentioning
confidence: 99%
“…Zhao et al [ 26 ] (2023) applied Graph Neural Networks (GNN) to predict basketball game outcomes by transforming structured data into unstructured graphs to reveal the complex passing interactions among players. By integrating machine learning algorithms with Graph Convolutional Network (GCN) models, they achieved a prediction accuracy rate of 71.54%, offering a novel perspective on team interactions.…”
Section: Related Studiesmentioning
confidence: 99%
“…Physical fitness refers to the basic athletic ability of an athlete's body and is an important part of an athlete's competitive ability (Zhao et al, 2023). The physical development level of basketball players is determined by the development of body shape, physical function, and athletic quality.…”
Section: Competitive Ability Of Basketball Playersmentioning
confidence: 99%
“…Zhao and his team studied the routine teaching of footwork among students in the school's basketball elective course (Zhao et al, 2023). They found that in basketball teaching, whether it was the beginner or the proficiency period, the advance and defense movement exercises should be closely combined so the overall technique could be improved fast (Guo et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%